2010
DOI: 10.1007/s10812-010-9294-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of polarization switching in single-mode injection semiconductor lasers

Abstract: UDC 621.373.8 Various dynamic effects during polarization switching in single-mode semiconductor lasers are examined on the basis of a previously developed approach. This model is found to provide a good description of a wide range of experimentally observed phenomena. At the same time, it offers a simple and intuitive interpretation of the nature and character of polarization switching effects that is related to the formation dynamics of the laser radiation. Introduction.Although the sudden switching of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 22 publications
(47 reference statements)
1
7
0
Order By: Relevance
“…Despite the fact that in the work [12] has demonstrated that these processes have a minor effect on the dynamics of polarization formation, it would be better to exclude this factor. Second, the appearance of the plateau results in a monotonic (practically linear -see the results [8]) polarization variation during the pulse, thus making it possible to control, in the simplest fashion, the polarization characteristics of the output radiation. A polarization degree for the output radiation is defined in a standard way as …”
Section: Theoretical Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the fact that in the work [12] has demonstrated that these processes have a minor effect on the dynamics of polarization formation, it would be better to exclude this factor. Second, the appearance of the plateau results in a monotonic (practically linear -see the results [8]) polarization variation during the pulse, thus making it possible to control, in the simplest fashion, the polarization characteristics of the output radiation. A polarization degree for the output radiation is defined in a standard way as …”
Section: Theoretical Modelmentioning
confidence: 99%
“…A new phenomenological approach [7,8] has recently been suggested for describing the PS. In the framework of this approach, the process of formation of polarized radiation in a semiconductor laser is governed by orientational anisotropy of the amplification and/or loss factors.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations